2012
DOI: 10.1186/1748-717x-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative rectal cancer staging with phased-array MR

Abstract: BackgroundWe retrospectively reviewed magnetic resonance (MR) images of 96 patients with diagnosis of rectal cancer to evaluate tumour stage (T stage), involvement of mesorectal fascia (MRF), and nodal metastasis (N stage).Our gold standard was histopathology.MethodsAll studies were performed with 1.5-T MR system (Symphony; Siemens Medical System, Erlangen, Germany) by using a phased-array coil. Our population was subdivided into two groups: the first one, formed by patients at T1-T2-T3, N0, M0 stage, whose un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Criteria based on border or signal intensity characteristics have proven more reliable than criteria based on size in determining nodal status. According to these criteria, MRI can be used to determine lymph node involvement with accuracy of 64-85% [1,9,15,18]. In this study the accuracy of N assessment for the two observers was 80.5% and 78.0%.…”
Section: Mri Of Primary Rectal Cancermentioning
confidence: 59%
“…Criteria based on border or signal intensity characteristics have proven more reliable than criteria based on size in determining nodal status. According to these criteria, MRI can be used to determine lymph node involvement with accuracy of 64-85% [1,9,15,18]. In this study the accuracy of N assessment for the two observers was 80.5% and 78.0%.…”
Section: Mri Of Primary Rectal Cancermentioning
confidence: 59%
“…Likewise, MRI offers an 81% overall accuracy compared with histological findings for T and N staging [6]. Due to these imperfect results of CI studies, authors have investigated new preoperative imaging modalities for colorectal cancer; some authors suggest the use of PET/CT as an alternative option [15,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although technical refinements have provided better quality for conventional imaging (CI) studies such as multi detector computed tomography (MDCT) and magnetic resonance imaging (MRI), complete correct preoperative staging has not yet been obtained. A recent study showed that the overall accuracy of MDCT was 86% in T staging and 84% in N staging [5]; another study reported that MRI provided an 81% overall agreement with histological findings for the T and N stages [6]. …”
Section: Introductionmentioning
confidence: 99%
“…It is much lower compared with the results by Al-Sukhni et al [16] (77%, 94% and 56.1, respectively), which is the latest study and also has the largest amount of patients among the three previous meta-analyses [14,15,16]. The following factors could have caused these differences: first, neo-ChRT is probably the most important factor; second, we only included studies that used a definition of MRF+ at ≤1 mm both in MRI and histopathology, and third, we have included studies that were published after Al-Sukhni's study [21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%